Investigations of power quality disturbances in a variable speed parallel pumping system with grid tied solar PV. (July 2018) - Shankar, V.K. Arun; Umashankar, S.; Sanjeevikumar, P.; Viliam, Fedák; Ramachandaramurthy, Vigna K.; Mihet-Popa, Lucian
Abstract: Energy use in water supply systems represents a significant portion of the global energy consumption. The electricity consumption due to the water pumping represents the highest proportion of the energy costs in these systems. The main objective of this paper is to observe the different power quality issues generated at the point of common coupling of a grid tied PV supplying power to the pumping motor for different preset pressures and taking readings at different loading conditions. The obtained results have been analyzed and valid conclusion is made on various power quality issue parameters like harmonics, voltage sag or swells levels etc. At the end suitable mitigation techniques to solve the PQ issues in a grid tied PV has been proposed.